“Confined Eutectic” Strategy for Visual Refrigeration Responsive Fluorescent Materials with Easy Preparation and Multi‐Color Tunability - Jifang Zhao; Jiahui Du; Tianyou Qin; Sean Xiao‐An Zhang; Lan Sheng (Advanced Science, 2025)
Abstract The temperature response window is a very critical parameter for evaluating temperature sensing performance of thermofluorochromic materials, and its regulation has long been a key focus in this field. Especially, the indication of refrigeration temperature is of great significance as it relates to public health and food safety. However, developing fluorochromic materials capable of visually reading out refrigeration temperature remains challenges. Herein, a “confined eutectic” strategy is proposed to develop fluorochromic materials that are easy to prepare and can naked‐eye recognition of refrigeration temperature. Through supramolecular interactions between dopant and host matrix, eutectic micro‐domains are formed and their crystallization point is effectively lowered into the range of 0–10 °C. The excellent crystalline host matrix provides a “confinement” effect, and thereby enhancing the crystallinity of the eutectics, which enables precise aggregation and dispersion of surrounding fluorophores, resulting in significant color changes. The mechanism is validated through variable‐temperature fluorescence spectra, confocal laser scanning microscopy and phase diagram analysis. The obtained materials exhibit high fluorescence color contrast, and can apply to diverse dyes for multi‐mode and multi‐color readout. This work not only open up new insights for refrigeration temperature responsive fluorochromic materials, but also provides a new way for visual regulation crystallinity.